تقييم أداء المصارف باستخدام نموذج التقييم المصرفي (CAMELS) - أسعد بسام (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research aims to evaluate the banks performance by applying the American Banking Evaluation system (CAMELS) on a sample of private banks, that is , bank of Bemo Saudi French and bank of Syria and overseas in order to assess the performance of banks through a case study to identify the weakness and strengths areas on its performance and identify the banking risks that constitute weakness points in the financial, operational and administrative transactions of the bank, which requires paying a special care and determining the required supervision preferences or the authority interference to manipulate the matter. The research has used the descriptive approach (case study) by collecting and analyzing the published financial data during study period (2015-2016) of both banks. The result of applying the (CAMELS) system on banks through the period of study indicates that, Bemo Bank has obtained the third Level (Rating "3") as per the compound evaluation policy of (CAMELS) system, which is means that , the Bank faces weaknesses in some elements, that are, assets quality, management that require a a special care and procedures should be taken by the bank ’s management in order to improve the performance of these elements and the performance of the bank as a whole. The results indicate as well that, the bank of Syria and overseas has obtained the second level (Rating "2") which means that the bank has a good performance in most its areas and good ability to face the challenges and require some procedures that can enhance the performance. The research showed the importance of applying (CAMELS) system through making comprehensive analysis for the performance of the bank and comparing this performance with the predetermined measures of (CAMELS) where by doing so it will be helpful for the management to conduct an accurate policy and plan through concentrating on the negative elements that need especial care. هدف البحث هو تطبيق نموذج التقييم المصرفي CAMELS من أجل الوقوف على المركز المالي للمصارف وتقييمها بما يخدم عملية تقويم الأداء, وذلك من خلال دراسة حالة عينة من المصارف الخاصة متمثلة ببنك بيمو السعودي الفرنسي وبنك سورية والمهجر من أجل تحديد مواطن القوة والضعف في الأداء وتحديد المخاطر المصرفية التي تشكل نقاط ضعف في العمليات المالية والتشغيلية والإدارية للمصرف، والتي تتطلب بذل عناية خاصة وتحديد أولويات التقويم اللازمة. وقد تم استخدام المنهج الوصفي من خلال جمع البيانات المالية المنشورة خلال الفترة (2015-2016) لكل من المصرفين موضوع البحث وتطبيق نموذج التقييم المصرفي CAMELS علي هذه البيانات. وأشارت نتائج تطبيق هذا النموذج خلال فترة الدراسة إلى حصول بنك بيمو والسعودي الفرنسي على درجة التصنيف /3/ بحسب التقييم المركب لنموذج CAMELS مما يعني أن أداء المصرف يواجه نقاط ضعف في بعض العناصر مثل جودة الأصول والإدارة والتي تستوجب اتخاذ إجراءات خاصة بهدف تحسين أداء هذه العناصر بصورة خاصة وأداء المصرف بصورة عامة. كما تشير النتائج إلى حصول بنك سورية والمهجر على درجة التصنيف \2 مما يعني أن أداء المصرف جيد في معظم النواحي وقدرته على مواجهة التحديات جيدة ويتطلب بعض الإجراءات التي من شأنها أن تحسن الأداء بصورة أفضل. وأظهر البحث أهمية تطبيق نموذج التقييم CAMELS من خلال إجراء تحليل شامل لأداء المصرف ومقارنته مع المقاييس المحددة من قبل النموذج الأمر الذي يساعد في رسم سياسة وخطط محكمة للإدارة من خلال التركيز على العناصر السلبية التي تحتاج إلى عناية خاصة.